Pola Komunikasi antara Guru dengan Orang Tua Siswa dalam Upaya Meningkatkan Parental Engagement selama Pembelajaran Alkitab di Rumah (Studi Kasus di Sekolah Sabat Gereja Yesus Sejati Solo) - Arvisha, Janice Clara; Yudiningrum, Firdastin Ruthnia (Jurnal Komunikasi Massa, 2025)
Research on communication in non-formal religious education is rarely conducted. However, non-formal religious education also has benefits that are just as important as formal education. Communication in education is considered important for creating good interactions between teachers and parents in order to achieve educational goals. One example of non-formal religious education is the Sekolah Sabat Gereja Yesus Sejati Solo, which hopes that interpersonal communication between teachers and parents can increase parental engagement. This study aims to identify patterns of interpersonal communication between teachers and parents in an effort to increase parental engagement during Bible study at home. The researcher uses Charles Osgood's message or stimulus-response theory, which states that verbal and nonverbal symbols conveyed in a certain way will stimulate others to respond. The researcher also uses Devito's concept of communication patterns, which divides communication patterns into primary, secondary, linear, and circular. This study is a descriptive qualitative study with a case study approach. The data collection technique used is interviews with teachers and parents. The results show that there are three communication patterns in interpersonal communication between teachers and parents: primary, secondary, and circular. These three communication patterns are sufficient to improve parental engagement. The communication obstacles found include a lack of face-to-face communication, difficulty understanding social media messages, a lack of empathy shown by teachers, and a lack of personal space in communication. These obstacles need to be addressed immediately so that the communication goal of improving parental engagement can be optimized.